Scaffolding Function of PI3Kgamma Emerges from Enzyme's Shadow. Issue 6 (24th March 2017) - Mohan, Maradumane L; Naga Prasad, Sathyamangla V
Abstract: Traditionally, an enzyme is a protein that mediates biochemical action by binding to the substrate and by catalyzing the reaction that translates external cues into biological responses. Sequential dissemination of information from one enzyme to another facilitates signal transduction in biological systems providing for feed-forward and feed-back mechanisms. Given this viewpoint, an enzyme without its catalytic activity is generally considered to be an inert organizational protein without catalytic function and has classically been termed as pseudo-enzymes. However, pseudo-enzymes still have biological function albeit non-enzymatic like serving as a chaperone protein or an interactive platform between proteins. In this regard, majority of the studies have focused solely on the catalytic role of enzymes in biological function, overlooking the potentially critical non-enzymatic roles. Increasing evidence from recent studies implicate that the scaffolding function of enzymes could be as important in signal transduction as its catalytic activity, which is an antithesis to the definition of enzymes. Recognition of non-enzymatic functions could be critical, as these unappreciated roles may hold clues to the ineffectiveness of kinase inhibitors in pathology, which is characteristically associated with increased enzyme expression. Using an established enzyme phosphoinositide 3-kinase γ, we discuss the insights obtained from the scaffolding function and how this non-canonical role could contribute to/alter the outcomes in pathology like cancer and heart failure. Also, we hope that with this review, we provide a forum and a starting point to discuss the idea that catalytic function alone may not account for all the actions observed with increased expression of the enzyme. Graphical Abstract: Highlights: Enzymes harbor tertiary structures providing non-catalytic docking sites for proteins. Docked proteins are kinase-independently regulated by enzymes. Enzyme scaffolded proteins could be recruited to non-classical sites or sequestered. Kinase-independent function could synergize or antagonize with kinase activity. Kinase inhibitors may need reconsideration in view of kinase-independent function.